A review on strategies for smoking cessation and the management of nicotine dependence - Abdullah, Marwah Y.; Alsaleh, Eman H.; Alkhulaiwi, Naima A.; Almalki, Mayssan H.; Zamil, Bayan T.; Alenezi, Abdassalam F.; Alferaih, Abdulaziz K.; Ahmed, Mahir A.; Mehawish, Safaa F.; Khalifa, Khalid A. (International Journal Of Community Medicine And Public Health, 2024)
This review explores strategies for smoking cessation and the management of nicotine dependence, focusing on behavioural treatments, pharmacotherapies, and the integration of both approaches. Smoking is a major contributor to numerous health conditions, and effective cessation strategies are vital for improving public health outcomes. Current evidence-based treatments include individual, group, and telephone counselling, along with Food and Drug Administration (FDA) - approved pharmacotherapies, which have proven successful across diverse populations, including those with low socioeconomic status or comorbid conditions. Nicotine dependence, recognized as a chronic and relapsing condition, requires systematic treatment approaches in healthcare settings. Behavioural therapies, such as cognitive behavioural therapy (CBT), motivational interviewing, and acceptance and commitment therapy (ACT), show efficacy in addressing both the physiological and psychological aspects of nicotine addiction. Combining these interventions with pharmacotherapies often yields the highest cessation rates. The review highlights the importance of personalized treatment plans that consider individual motivations, socioeconomic factors, and the chronic nature of nicotine dependence, advocating for comprehensive approaches to smoking cessation.